Considerations about the "Virgilian century" (Minerva, 2021)
The scholar Joseph Farrell defined the past century as “the Virgilian century”, due to the notability that the poet from Mantua achieved in Classical Studies. This paper undertakes an overview of some of the interpreters of the Aeneid in the 20th century to show the reasons that can justify the conclusion by Farrell. The conclusion of this paper leads to establish a close relationship between Virgil’s academic prestige in the 20th century and the rise of certain and concurring currents of literary criticism.
Keywords: Virgil; Aeneid; literary criticism; 20th century